Apparent Shear Sensitivity of Molecular Rotors in Various Solvents - Mustafic, Adnan; Elbel, Kristyna M.; Theodorakis, Emannuel A.; Haidekker, Mark (Journal of fluorescence, 2015)
Fluorescent environment-sensitive dyes often change their spectral properties concomitantly with multiple solvent properties, such as polarity, protonation, hydrogen bond formation, or viscosity. Careful consideration of the response is needed when a fluorescent dye is used to report a single property. Recently, we observed an increase of emission intensity of viscosity-sensitive molecular rotors in fluids subject to flow and speculated that either polar-polar interaction or hydrogen bond formation play a role in the apparent flow sensitivity. In this study, we show experimental evidence that photoisomerization to an isomer with a lower quantum yield, first proposed by Rumble et al. (J Phys Chem A 116(44):10786–10792, 2012 ), plays a key role in the observed phenomenon. We subjected four molecular rotors with different electron acceptor motifs to fluid flow in solvents of different polarity and ability to form hydrogen bonds. We also measured the isomerization dynamics in a custom fluorophotometer with extremely low light exposure. Our results indicate that the photoisomerization rate depends both on the solvent and on the electron acceptor group, as does the recovery of the original isomer in the dark. In most solvents, recovery of the dark isomer is much more rapid than originally reported, and a state of quasi-equilibrium between both isomers is possible. Moreover, the sensitivity (i.e., relative intensity increase at the same flow rate) is also solvent-dependent. The intensity increase can be detected at very low velocities (as low as 0.06 mm/s). Characteristic for fluorescent dyes is the high spatial resolution, and no flow measurement device with comparable sensitivity and spatial resolution exists, although the nature of the solvent needs to be taken into account for quantitative flow measurement.